Infant Oral Mutilation - Emily A. Pope; Michael W. Roberts; E. LaRee Johnson; Clark L. Morris (Hindawi Limited, 2018)
Ebinyo refers to the practice of removing primary canine tooth follicles in infants without anesthetic by African traditional healers or elders using unsterilized instruments. This report describes a case of ebinyo or infant oral mutilation (IOM) and associated sequelae in a child adopted from a remote African tribe. The intraoral examination revealed that the patient was missing his primary maxillary and mandibular canines. The maxillary anterior periapical radiograph displayed a dysmorphic ectopic unerupted maxillary right primary canine positioned mesial to the maxillary right primary first molar. Periapical films taken confirmed partial or complete absence of the patient's primary mandibular left (73) and mandibular right (83) canines, and a bitewing and periapical film confirmed the absence of the patient's primary maxillary left (63) canine. The permanent canines will be monitored for possible hypoplasia secondary to trauma to the tooth buds during extirpation of the primary canines. Research presented in this report reveals that there are serious health implications involved with the practice of ebinyo.